Innovative Approaches and Solutions in Advanced Intelligent Systems - Margenov, Svetozar; Angelova, Galia; Agre, Gennady (Studies in Computational Intelligence, 2016)
This volume is a selected collection of papers presented and discussed at the International Conference "Advanced Computing for Innovation (AComIn 2015)". The Conference was held at 10th -11th of November, 2015 in Sofia, Bulgaria and was aimed at providing a forum for international scientific exchange between Central/Eastern Europe and the rest of the world on several fundamental topics of computational intelligence. The papers report innovative approaches and solutions in hot topics of computational intelligence - advanced computing, language and semantic technologies, signal and image processing, as well as optimization and intelligent control.